Peningkatan Kekerasan Dalam Rumah Tangga (Kdrt) Selama Pandemi Covid-19 Dalam Kacamata Sosiologi Hukum Increase in Domestic Violence (KDRT) During the Covid-19 Pandemic in Legal Sociology - Sriyanti; Edi Pranoto (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2024)
The Covid-19 pandemic has had quite a big impact on human life, including in the fields of education, economy, culture and society. Unplanned presence forces the community to adapt to existing changes. Starting from the largest unit, namely the country, down to the smallest unit, namely the family, there are problems being faced due to the Covid-19 pandemic. One of the phenomena that occurred was the increase in Domestic Violence (KDRT), which doubled the number from previous years. Even though the law on the elimination of domestic violence has been formed to address the problem of domestic violence. This research aims to describe the phenomenon of increasing domestic violence during the Covid-19 pandemic from a socio-legal perspective. The research method is qualitative with a literature study approach. Research results show that the increase in cases of domestic violence during the Covid-19 pandemic was caused by large-scale social restrictions, often abbreviated as PSBB, which required victims, namely women or wives, to remain with the perpetrators of violence, namely men or husbands. Economic problems are one of the factors that can give rise to conflict between husband and wife which leads to violence, differences, culture, infidelity, etc. Forms of domestic violence include physical, economic, psychological violence and household neglect. The conclusion from the research is that the Law on the Elimination of Domestic Violence cannot truly eradicate domestic violence because victims often do not report it to the authorities due to the strong patriarchal culture.